Teaching Old Testament Studies In Zimbabwe’s Theological Institutions In The HIV/AIDS Era - Togarasei, Lovemore (Zimbabwe Journal of Educational Research, 2002)
There is no doubt that HIV/AIDS is humanity’s greatest enemy in this century. Millions of people have been affected and infected by this disease. In Zimbabwe statistics have it that about 2000 people die of HIV/AIDS related diseases every week. A lot of resources are spent in caring for the infected and the affected. With this scenario, HIV/AIDS no longer has to be seen as a medical problem.- It is now a social problem and so every sector of the society has to think deeply on how it can 'make a difference' in dealing with HIV/AIDS. This article argues that the teaching of Biblical Studies in Zimbabwe's theological institutions should be geared towards addressing the problem. It argues for the centrality of Biblical Studies in both theological institutions and Christian societies.' It shows how the Bible has been used to address human problems and how a Biblical studies course taking cognisancy of the HIV/AIDS problem can be rewarding. It ends by suggesting some topics and instructional methodologies to be used in teaching Biblical Studies in Zimbabwe's theological institutions in the era of HIV/AIDS.
Free